Family Acmaeidae (Gastropoda, Archaeogastropoda) in Peru - Paredes, Carlos (1980)
This paper deal with seven species of Acmaeidae Scurria viridula (Lamarck), S. parasitica (Orbigny), S. variabilis (Sowerby), S. zebrina (Lesson), Collisella orbignyi (Dall), C. ceciliana (Orbigny) and C. araucana (Orbigny) reported along the rocky along Lima Department. Information concerned with geographical and vertical distribution, and others ecological data are also added.